PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Perusahaan Pertambangan yang terdaftar di BEI) - Sri Mulyani; Anita Wijayanti; Endang Masitoh (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2018)
The purpose of this research is to know the influence of institutional ownership, independent commissioner, audit committee and audit quality to tax avoidance at mining company listed on BEI year 2014-2016. The population of this study is mining companies listed on the BEI 2014-2016 as many as 46 companies. Sampling used in this research purposive sampling method. Data source is secondary data obtained from company website and BEI website (www.idx.co.id). This study uses multiple regression analysis to analyze data with the help of SPSS 21 edition program. The results of this study indicate that the variables of institutional ownership, audit committee and audit quality have significant influence on tax avoidance, while independent commissioner variable has no significant effect on tax avoidance. The results of this study are expected to be an additional consideration of the management in conducting tax avoidance is correct and efficient without violating applicable tax laws, and can provide additional information for users of financial statements in investment decision making